Marine renewable energy for Arctic observations - Ruth Branch; Fadia Ticona Rollano; Emma Cotter; James R. McVey; Robert J. Cavagnaro; Ignatius Rigor (Frontiers in Marine Science, 2022)
Arctic observations are becoming increasingly valuable as researchers investigate climate change and its associated concerns, such as decreasing sea ice and increasing ship traffic. Networks of sensors with frequent sampling capabilities are needed to run forecast models, improve navigation, and inform climate research. Sampling frequency and deployment duration are currently constrained by battery power limitations. In-situ power generation using marine renewable energy sources such as waves and currents can be used to circumvent this constraint. Wave and current resources vary spatially and temporally in the Arctic, with some locations and seasons being better suited for marine renewable energy power generation. Locations and seasons with small resources may still be able to use marine renewable energy because of the low power requirements of the instruments. In this study, we describe the wave and current resources in the Arctic, outline the electricity generation developments that are needed to utilize the resources, and suggest use cases. Wave and current energy converters developed to power observations in the Arctic could also be used to power observations at lower latitudes. Marine renewable energy has the potential to decrease dependence on batteries and improve data collection capabilities in the Arctic; however, this would require the development of new low power technologies that can operate in extreme Arctic environments.

Float Your Boat: Launching Students into the Arctic Ocean - David Forcucci; Ignatius Rigor; Wendy Ermold; Harry Stern (Oceanography, 2022)

Observing Arctic Sea Ice - Melinda Webster; Ignatius Rigor; Nicholas Wright (Oceanography, 2022)
Our understanding of Arctic sea ice and its wide-ranging influence is deeply rooted in observation. Advancing technologies have profoundly improved our ability to observe Arctic sea ice, document its processes and properties, and describe atmosphere-ice-ocean interactions with unprecedented detail. Yet, our progress toward better understanding the Arctic sea ice system is mired by the stark disparities between observations that tend to be siloed by method, scientific discipline, and application. This article presents a review and philosophical design for observing sea ice and accelerating our understanding of the Arctic sea ice system. We give a brief history of Arctic sea ice observations and showcase the 2018 melt season within the context of five observational themes: spatial heterogeneity, temporal variability, cross-disciplinary science, scalability, and retrieval uncertainty. We synthesize buoy data, optical imagery, satellite retrievals, and airborne measurements to demonstrate how disparate data sets can be woven together to transcend observational-scale issues. The results show that there are limitations to interpreting any single data set alone. However, many of these limitations can be surmounted by combining observations that cross spatial and temporal scales. We conclude the article with pathways toward coordinating across observational platforms in order to: (1) optimize the scientific, operational, and community return on observational investments, and (2) facilitate a richer understanding of Arctic sea ice and its role in the climate system.

Changes in Arctic Ocean Circulation from In Situ and Remotely Sensed Observations: Synergies and Sampling Challenges - James Morison; Ron Kwok; Ignatius Rigor (Oceanography, 2022)
Both in situ and remote sensing observations of Arctic Ocean hydrography and circulation have improved dramatically in recent decades, and combining the two can yield the most complete picture of Arctic Ocean change. Recent results derived from classical hydrography and satellite ocean altimetry illustrate this synergy and also reveal a fundamental in situ sampling challenge.

An Overview of Ocean Climate Change Indicators: Sea Surface Temperature, Ocean Heat Content, Ocean pH, Dissolved Oxygen Concentration, Arctic Sea Ice Extent, Thickness and Volume, Sea Level and Strength of the AMOC (Atlantic Meridional Overturning Circulation) - Carlos Garcia-Soto; Lijing Cheng; Levke Caesar; S. Schmidtko; Elizabeth B. Jewett; Alicia Cheripka; Ignatius Rigor; Ainhoa Caballero; Sanae Chiba; Jose Carlos Báez; Tymon Zielinski; John Patrick Abraham (Frontiers in Marine Science, 2021)
Global ocean physical and chemical trends are reviewed and updated using seven key ocean climate change indicators: (i) Sea Surface Temperature, (ii) Ocean Heat Content, (iii) Ocean pH, (iv) Dissolved Oxygen concentration (v) Arctic Sea Ice extent, thickness, and volume (vi) Sea Level and (vii) the strength of the Atlantic Meridional Overturning Circulation (AMOC). The globally averaged ocean surface temperature shows a mean warming trend of 0.062 ± 0.013°C per decade over the last 120 years (1900–2019). During the last decade (2010–2019) the rate of ocean surface warming has accelerated to 0.280 ± 0.068°C per decade, 4.5 times higher than the long term mean. Ocean Heat Content in the upper 2,000 m shows a linear warming rate of 0.35 ± 0.08 Wm –2 in the period 1955–2019 (65 years). The warming rate during the last decade (2010–2019) is twice (0.70 ± 0.07 Wm –2 ) the warming rate of the long term record. Each of the last six decades have been warmer than the previous one. Global surface ocean pH has declined on average by approximately 0.1 pH units (from 8.2 to 8.1) since the industrial revolution (1770). By the end of this century (2100) ocean pH is projected to decline additionally by 0.1–0.4 pH units depending on the RCP (Representative Concentration Pathway) and SSP (Shared Socioeconomic Pathways) future scenario. The time of emergence of the pH climate change signal varies from 8 to 15 years for open ocean sites, and 16–41 years for coastal sites. Global dissolved oxygen levels have decreased by 4.8 petamoles or 2% in the last 5 decades, with profound impacts on local and basin scale habitats. Regional trends are varying due to multiple processes impacting dissolved oxygen: solubility change, respiration changes, ocean circulation changes and multidecadal variability. Arctic sea ice extent has been declining by −13.1% per decade in summer (September) and by −2.6% per decade in winter (March) during the last 4 decades (1979–2020). The combined trends of sea ice extent and sea ice thickness indicate that the volume of non-seasonal Arctic Sea Ice has decreased by 75% since 1979. Global mean sea level has increased in the period 1993–2019 (the altimetry era) at a mean rate of 3.15 ± 0.3 mm year –1 and is experiencing an acceleration of ∼ 0.084 (0.06–0.10) mm year –2 . During the last century (1900–2015; 115y) global mean sea level (GMSL) has rised 19 cm, and near 40% of that GMSL rise has taken place since 1993 (22y). Independent proxies of the evolution of the Atlantic Meridional Overturning Circulation (AMOC) indicate that AMOC is at its weakest for several hundreds of years and has been slowing down during the last century. A final visual summary of key ocean climate change indicators during the recent decades is provided.

Polar Ocean Observations: A Critical Gap in the Observing System and Its Effect on Environmental Predictions From Hours to a Season - Gregory C. Smith; Richard Allard; Marcel Babin; Laurent Bertino; Matthieu Chevallier; Gary Corlett; Julia Crout; Fraser Davidson; Bruno Delille; Sarah T. Gille; David Hebert; Patrick Hyder; et al. (Frontiers in Marine Science, 2019)

Autumn atmospheric preconditioning for interannual variability of wintertime sea-ice in the Okhotsk Sea - Yoshi N. Sasaki; Yurika Katagiri; Shoshiro Minobe; Ignatius G. Rigor (Journal of Oceanography, 2007)